Effect of soil-foundation-structure interaction on fundamental frequency of RC chimneys - Jayalekshmi, B.R.; Menon, Devdas (Journal of Structural Engineering, 2024)
The construction of tall reinforced concrete chimneys has been increasing, worldwide, in recent times due to industrialization. These tall and slender structures are usually wind-sensitive, requiring a dynamic analysis, to account for a proper assessment of responses under along-wind and across-wind directions and also under seismic loading. The modelling is usually carried out assuming the base (usually raft foundation supported on soil) as fixed. However, in reality, the base is compliant, due to compressibility of the soil, and this can significantly alter the dynamic characteristics of the chimney. This paper presents a comprehensive assessment of modification in the fundamental natural frequency of tapered RC chimneys in the height range of 100m to 400m due to the effect of soil-foundation–structure interaction (SFSI) through a parametric study. The parameters considered for the investigation are the height to mean base diameter ratio of the chimney, rigidity of raft foundation and the flexibility of soil. The flexibility of the supporting soil is represented by a series of Winkler springs, attached to the bottom of the raft foundation, corresponding to soft, medium and hard soils. The results of modal analysis of the three dimensional finite element model of the integrated soil-raft foundation-chimney system are compared with that of a chimney with fixed base.